Pengaruh Kombinasi Jenis Pupuk Kandang dan Tingkat Kehalusan Zeolite pada Pertumbuhan Bibit Kakao (Theobroma cacao L.) - Ayu Mega Parama; Rijadi Subiantoro; Fatahillah Fatahillah (Politeknik Negeri Lampung, 2020)
Providing manure can not only increase the availability of nutrients but also support the growth of microorganisms. Zeolite has a high CEC, which results in the media being able to bind water and nutrients added to the soil. This study aims to get the best type of manure on cocoa seedling growth, get the effect of zeolite smoothness on the growth of cocoa seedlings, and find out the interaction of the composition of manure and zeolite on the growth of cocoa seedlings. The research was conducted at Experimental Garden of Politeknik Negeri Lampung, from December 2017 to May 2018. The method used was the factorial pattern randomized block design (RBD) which consisted of two factors. The first factor consists of three levels, namely without manure, 200 g chicken manure, and 200 g goat manure. The second factor consisted of three levels, namely zeolite size (without zeolite, zeolite size 30 mesh, and zeolite size 16 mesh). Observation variables were plant height, leaves number, stem diameter, shoot dry weight, soil pH, and soil CEC. The results showed that manure did not show an effect on plant height, stem diameter, and leaves number, but had an effect on soil pH and soil CEC. The level of zeolite smoothness does not affect plant height, stem diameter, leaves number, and soil pH, but affects soil CEC the 16 mesh size of compared to 30 mesh size. There is no interaction on types of manure and size of zeolite fineness of plant height, stem diameter, leaves number, shoot dry weight, soil soil pH, and soil CEC.